Simulating the impact of climate change on yield reduction of vegetable crop propagation (2010)
Effects of climate change on the yield reduction and prediction of vegetable crop was carried out using CROPWAT 8 with irrigation scheduling conditions; critical depletion at a water application depth of 2 mm, definite intervals of 3 days at a depth of 2 mm and no irrigation. The model was run with 9 year weather records for Ibadan, Nigeria spanning 2000 to 2008, the yearly weather records was divided into quarterly records depicting vegetable crop growth period from planting to harvesting. Quarterly growth season of January- April (1), April- July(II), July- October (III), October- January(IV) for the vegetable crop with an increase in temperature rise at each 1C. Simulation results analyses for 2000-2008 under critical depletion reveals that each 1C temperature rises from ambient condition to 3 C, yield reduction for season I ranges from 4.3% to 27.1%, 0%-0.2% for season II, 0% for season III and increasing to 7.1% to 15.9% for season IV. Also, from the prediction analysis (2009-2013) obtained from SPSS a statistical tool and the method of Least Square Deviation (LSD), for ambient weather condition of the study location there are higher yield reduction from 9% to 11.68% for season I, 0.1% to 0.77% for season II, 0% to 0.76% for season III and 12.2% to 12.0% for season IV respectively. Hence, climate change has impacted negatively on higher predicted yield reductions of three out of the four seasons considered from year 2009 to 2013.